COMMUNITY MOTIVATION TOWARDS JOGGING IN THE ATLETIC FIELD OF GOR TRI STRENGTH COMPETITION IN SEMARANG CITY DURING THE COVID-19 PANDEMIC - Ayu Pramahesti Dhinisya; Setya . Rahayu; Henny . Setyawati; Fatona . Suraya (Nusa Cendana University, 2022)
During the Covid-19 pandemic, the main thing to pay attention to is maintaining health, one of which is jogging. Jogging is a simple sport usually done by the community. GOR Tri Competition Juang facilities from the government as a free sports venue. The purpose of this study was to find out the community's motivation for jogging during the pandemic at the Tri Lomba Juang GOR, Semarang city. This study uses a qualitative descriptive approach. Data collection is simple random sampling, data collection techniques using observation, interviews and documentation. The target of this research is the people of Semarang city doing jogging activities on the athletic field of the Tri Competition Juang GOR. The results of the research on the motivation of the people of the city of Semarang towards jogging during the Covid-19 pandemic came from intrinsic and extrinsic factors. Higher intrinsic factor, respondents were motivated from within to jog during the pandemic. While extrinsic factors are lower because of encouragement from family and friends. The public's understanding of the benefits of jogging during a pandemic is explained for health during a pandemic such as increasing endurance, body immunity, and avoiding stress during the Covid-19 pandemic. The conclusion of the study is that the motivation of the people of Semarang to jogging during the Covid-19 pandemic is that the intrinsic factor is higher than the extrinsic factor. Public understanding of the benefits of jogging during a pandemic for body health and coping with stress.